Respuesta :
The explicit rule for the geometric sequence is in the form,
an = (a1)^(r -1)
where an is the nth term, a1 is the first term, and r is the common ratio. Substituting the known terms from the given above, we arrive to the explicit form of the sequence which is,
an = 49^(3 - 1)
an = (a1)^(r -1)
where an is the nth term, a1 is the first term, and r is the common ratio. Substituting the known terms from the given above, we arrive to the explicit form of the sequence which is,
an = 49^(3 - 1)